Role of p34cdc2-mediated phosphorylations in two-step activation of pp60c-src during mitosis. - Shenoy, S (1992)
Phosphorylation of pp60c-src by p34cdc2 at three amino-proximal serine/threonine residues is temporally correlated with, but insufficient for, mitotic activation of c-Src kinase. The direct cause of activation during mitosis appears to be temporally correlated partial dephosphorylation of Tyr-527, a residue whose phosphorylation strongly suppresses pp60c-src activity. Site-directed mutagenesis of the serine/threonine phosphorylation sites blocks half the mitosis-specific decrease in Tyr-527 phosphorylation and half the increase in pp60c-src kinase activity. We conclude that p34cdc2 partially activates pp60c-src by a two-step process in which its serine/threonine phosphorylations either sensitize pp60c-src to a Tyr-527 phosphatase or desensitize it to a Tyr-527 kinase. Furthermore, additional events, independent of these p34cdc2-mediated phosphorylations, participate in mitotic activation of pp60c-src.